Solid Waste Management – A Study on the Problems Faced By Hotels in the Municipalities of Kerala - P. S. Ajith and P. N. Harikumar (Commerce Spectrum, 2015)
Municipal Solid Waste Management is fast becoming a social menace in Kerala. Extreme scarcity of free space for landfilling acts as a hurdle for Local Bodies to dispose waste. The rapid population growth overwhelms the capacity of Municipalities in the State to offer even the very basic solid waste services. Being, a major waste contributor in Municipal limits, Solid Waste Management of hotels is an area deserving special attention of Authorities. The main objective of the study is to know the physical and chemical composition of Municipal Solid Waste in the State and major problems faced by hotels operating in each Region and Area to which the Municipalities belong. By Random Sampling method 173 hotels belonging to different Municipalities are selected to identify the major problems faced by them and a Structured Questionnaire was administered to collect the primary data. The study reveals that the Average Density of Municipal Solid Waste 3 is 541.63 Kg/M , the Average Moisture Content is 55.74 per cent, Average Calorific Value is 1638.75 K.Cal/Kg and Average Ph is 7.31. Through a Factor Analysis seven factors are identified such as Environmental Management Issues, Waste Collection Issues, Waste Disposal Issues, Negative Impact of Waste Management, Limitations of Waste Management, Support from Government and Private Participation. As a concept Integrated Solid Waste Management will find solutions to the manifold problems persisting in Kerala.